Seeking Harmony over Punishment: Restorative Justice Approaches to Domestic Violence in Islamic and Indonesian Legal Frameworks - Fauzi, Inna; Ismayawati, Any; Hanani, Azka (UIN Sunan Kalijaga Yogyakarta, 2023)
Domestic violence in its various forms occured, yet often victims of violence are reluctant to separate from their perpetrators. Reasons such as social, economic, and religious considerations to maintain the household make some victims of domestic violence withdraw their reports and forgive the perpetrators for the sake of household continuity. This research aims to answer what is the perspective of restorarive jastice in Islam and Indonesian national law in domestic violence cases? This research was conducted using a literature research method that explores relevant data in relation to this topic. This research used juridical-normative approach, which then analyzes the data using the concept of restorative justice in Islam and Indonesian national law.The results show that based on the restorative justice system, both in Islam and Indonesian national law, both provide opportunities for perpetrators and victims to restore conflict. The difference is that the concept of restorative justice in Islam emphasizes God's rights and human rights.So that the output can be in the form of victim forgiveness, as well as diyat (fine) sanctions for the perpetrator. Meanwhile, in the restorative justice system of Indonesian state law, it no longer focuses on the concept of imprisonment. Furthermore, this regulation aims for preventive, protective, repressive, and consolidative efforts. This article is limited to an overview of the comparison of restorative justice systems in Islam and Indonesian national law in handling domestic violence cases theoretically.[Kekerasan Dalam Rumah Tangga (KDRT) dalam berbagai bentuknya sering terjadi, namun seringkali korban kekerasan enggan untuk berpisah dengan pelaku. Alasan seperti kebutuhan sosial, ekonomi, dan pertimbangan agama untuk mempertahankan rumah tangga membuat beberapa korban KDRT mencabut laporan mereka dan memaafkan pelaku demi kelangsungan rumah tangga. Penelitian ini bertujuan untuk menjawab bagaimana perspektif restorarive jastice dalam Islam dan hukum nasional Indonesia dalam kasus kekerasan domestik?. Penelitian ini dilakukan dengan menggunakan metode penelitian pustaka yang menggali data relevan sehubungan dengan topik ini. Penelitian ini mengadopsi pendekatan yuridis-normatif secara umum, yang kemudian menganalisis data dengan menggunakan konsep restorative justice dalam Islam dan hukum nasional Indonesia. Hasil penelitian menunjukkan bahwa berdasarkan sistem restorative justice, baik dalam Islam dan hukum nasional Indonesia, sama-sama memberikan kesempatan bagi pelaku dan korban untuk memulihkan konflik. Bedanya, dalam konsep restorative justice Islam lebih menekankan pada hak Tuhan dan Hak manusia. Sehingga outputnya dapat berupa pemaafan korban, maupun sanksi diyat (denda) bagi pelaku. Sedangkan dalam sistem restorative justice hukum negara Indonesia, tidak lagi fokus pada konsep pemenjaraan. Lebih jauh, peraturan ini bertujuan untuk upaya prefentif, protektif, represif, dan konsolidatif. Artikel ini terbatas pada gambaran mengenai perbandingan restorative justice sistem dalam Islam dan hukum nasional Indonesia dalam menangani perkara kekerasan domestik secara teoretis.]